Pemaknaan Frasa “Untuk Sementara Berhalangan Menjalankan Jabatan” Dalam Undang-Undang Jabatan Notaris - Junana, W Ida; Yogantara S., Pande (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The purpose of this paper is to find out and examine the meaning of the phrase "temporarily unable to carry out his position as a Notary" and also to find out and examine the legal consequences for a Notary who is temporarily unable to carry out his position. The legal research method in this journal uses normative legal research, with a statutory approach and a conceptual approach. law. Based on the results of the study, the phrase "temporarily unable to carry out his position as a Notary" can be interpreted as being unable to do so due to overmacht conditions and unable to do so because the Notary holds positions as civil servants, state officials, advocates, or other positions. For a Notary who is temporarily unable to carry out his position, he can apply for leave with a maximum total leave of 12 (twelve) years. As for those who cause legal consequences, if the Notary does not apply for leave, he will be subject to sanctions in the form of respectful dismissal. However, the UUJN/UUJN-P does not stipulate sanctions if the Notary is on leave for more than 12 (twelve) years.